IMPLEMENTASI LKPD BERBASIS INKUIRI TERBIMBING PADA MATERI PENCEMARAN AIR UNTUK MELATIHKAN KETERAMPILAN BERPIKIR KRITIS SISWA SMP - Adin Muafiro; Elok Sudibyo (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2022)
This research was conducted to determine the effect of the application of guided inquiry-based students’ worksheets in practicing critical thinking skills on water pollution material. The type of research used is pre-experimental with one group pretest posttest design method. The research instrument used was a pretest posttest sheet, and a questionnaire. The subjects of this research were students of VII-A of SMPN 1 Deket Lamongan with a total of 29 students. The results in this study were based on an increase in the pretest posttest score. The average score of n-gain pretest posttest is 0,7 with moderate criteria. Increasing the percentage of critical thinking indicator, analyzing arguments from 25% to 73% with sufficient criteria, observing and writing down the result from 72% to 92% with very good criteria, making further explanations from 29% to 67% with sufficient criteria, and concluding from 14% to 75% with sufficient criteria. The average result of the percentage of completeness is 77% in the goog category and the average increase in the percentage of completeness of the critical thinking indicator gets a score of 2 with high criteria and students response questionnaires obtained result of 78% in the strong category. Thus, guided inquiry-based worksheets can train students critical thinking skills.